Collaborative governance model in disaster mitigation in Malang Regency - Asih Widi Lestari; Firman Firdausi; Yuli Indah Sari; Amanda Dewanata Puteri (Publisia: Jurnal Ilmu Administrasi Publik, 2024)
Indonesia is a country that has a disaster-prone geographic condition. This is because Indonesia is located at a confluence of tectonic plates, and the tropics have two seasons, namely rainy and dry. Disasters tend to occur in vulnerable communities, and will make communities more vulnerable. The vulnerability of a community begins with the unsafe physical, social and economic conditions attached to it. This insecure condition occurs due to internal and external dynamic pressure, for example in the local institutional community that is less developed and lacks the right skills. Disaster Management Policy is an integral part of national development, namely a series of disaster management activities before, during and after a disaster is carried out by the Malang Regency Government in its efforts to deal with frequent disasters which are not easy, in the implementation process many obstacles occur, disaster mitigation should routinely carried out to reduce the impact of disasters, and make people aware of disaster mitigation, one of which is by carrying out routine socialization on disaster mitigation starting from pre-disaster, during disaster and post-disaster, but BPBD Malang Regency rarely conducts outreach related to disaster mitigation, so that when disaster occurs Disaster impacts are far more severe and result in losses and cause casualties. Malang Regency Government needs to strengthen collaboration with other stakeholders for disaster mitigation efforts.